2015
DOI: 10.1080/19420862.2015.1105416
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of rheumatoid arthritis patients treated with itolizumab

Abstract: (2016) Immunological evaluation of rheumatoid arthritis patients treated with itolizumab, mAbs, 8:1, 187-195, DOI: 10.1080/19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 Rheumatoid arthritis is an autoimmune disease characterized by joint inflammation that affects approximately 1% of the general population. Itolizumab, a monoclonal antibody specific for the human CD6 molecule mainly expressed on T lymphocytes, has been shown to inhibit proliferation of T cells and proinflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…None of the tested doses was considered dose-limiting for this clinical indication (up to 0Á8 mg/kg administered weekly intravenously, 12 doses in total). In line with these results, itolizumab administration did not induce a measurable antiidiotypical antibody response, as also observed in previous studies [32,34,40].…”
Section: Discussionsupporting
confidence: 91%
“…None of the tested doses was considered dose-limiting for this clinical indication (up to 0Á8 mg/kg administered weekly intravenously, 12 doses in total). In line with these results, itolizumab administration did not induce a measurable antiidiotypical antibody response, as also observed in previous studies [32,34,40].…”
Section: Discussionsupporting
confidence: 91%
“…The present report is the first human study evaluating the effect of cholecalcipherol administration in eRA patients. Also standard treatment with MTX has no effect of Th cells subsets, previous studies showed an effect of MTX on activated T cells in vitro [48, 49], whereas in a recent paper patients treated with MTX administered orally in a dose ranging from 7 to 25 mg has no decrease in peripheral T cells count [50]. Our data confirm no effect of MTX in combination with GCs of different T cells sub-types.…”
Section: Resultssupporting
confidence: 78%
“…Analysis of a similar number of rheumatoid arthritis patients also showed a suppressive effect of itolizumab, enhancing methotrexate treatment . Unlike lymphocyte numbers, which were transiently reduced, the reduction of inflammatory cytokine production was sustained, suggesting a mechanism other than depletion …”
Section: Introductionmentioning
confidence: 91%
“…In a study of 26 psoriasis patients receiving multiple injections of the humanized version of ior t1, itolizumab, over the course of a year, the mAb was immunosuppressive; the reduction of the proliferation and production of pro‐inflammatory cytokines being statistically significant . Analysis of a similar number of rheumatoid arthritis patients also showed a suppressive effect of itolizumab, enhancing methotrexate treatment . Unlike lymphocyte numbers, which were transiently reduced, the reduction of inflammatory cytokine production was sustained, suggesting a mechanism other than depletion …”
Section: Introductionmentioning
confidence: 99%